GREEN ROOFS: MORE THAN JUST A PRETTY FACE - Jawad, Nida; Abidi, Dr. Syeda Raaeha Tuz Zahra; Jahangir, Dr. Amna Jahangir (Journal of Arts & Social Sciences, 2022)
Green Roof is basically a traditional concept which is revived and executed to focus and improve adverse effects of our urban environment. Benefits and impacts of green roof are not fully understood and valued. This paper reviews and discusses the different benefits of green roofs as solutions in reducing the energy, maintaining indoor temperatures, enhancing sound insulation and  fire resistance, increasing life span of the roof, providing green spaces in concrete jungles, reduction of UHI effects and improved air quality. In addition to all this green roof also increases the aesthetics of buildings and different research have shown that green roof also improves the energy performance of buildings in summers and winters.